Comparative Mapping and Targeted‐Capture Sequencing of the Gametocidal Loci in Aegilops sharonensis. Issue 2 (1st July 2017) - Grewal, Surbhi; Gardiner, Laura‐Jayne; Ndreca, Barbora; Knight, Emilie; Moore, Graham; King, Ian P.; King, Julie
Abstract : Gametocidal (Gc) chromosomes or elements in species such as Aegilops sharonensis Eig are preferentially transmitted to the next generation through both the male and female gametes when introduced into wheat ( Triticum aestivum L.). Furthermore, any genes, such as genes that control agronomically important traits, showing complete linkage with Gc elements, are also transmitted preferentially to the next generation without the need for selection. The mechanism for the preferential transmission of the Gc elements appears to occur by the induction of extensive chromosome damage in any gametes that lack the Gc chromosome in question. Previous studies on the mechanism of the Gc action in Ae. sharonensis indicates that at least two linked elements are involved. The first, the breaker element, induces chromosome breakage in gametes, which have lost the Gc elements while the second, the inhibitor element, prevents the chromosome breakage action of the breaker element in gametes which carry the Gc elements. In this study, we have used comparative genomic studies to map 54 single nucleotide polymorphism (SNP) markers in an Ae. sharonensis 4S shL introgression segment in wheat and have also identified 18 candidate genes in Ae. sharonensis for the breaker element through targeted sequencing of this 4S shL introgression segment. This valuable genomic resource will aide in further mapping the Gc locus that could be exploited in wheat breeding to produce new, superior varieties of wheat.